A Smartphone-Based Application Improves the Accuracy, Completeness, and Timeliness of Cattle Disease Reporting and Surveillance in Ethiopia - Beyene, Tariku Jibat; Asfaw, Fentahun; Getachew, Yitbarek; Tufa, Takele Beyene; Collins, Iain; Beyi, Ashenafi Feyisa; Revie, Crawford W. (Frontiers in Veterinary Science, 2018)
Accurate disease reporting, ideally in near real-time, is a prerequisite to detecting disease outbreaks and implementing appropriate measures for their control. This study compared the performance of the traditional paper-based approach to animal disease reporting in Ethiopia to one using an application running on smartphones. In the traditional approach the total number of cases for each disease or syndrome were aggregated by animal species and reported to each administrative level at monthly intervals; while in the case of the smartphone application demographic information, a detailed list of presenting signs, in addition to the putative disease diagnosis were immediately available to all administrative levels via a Cloud-based server. While the smartphone based approach resulted in much more timely reporting, there were delays due to limited connectivity; these ranged on average from 2 days (in well-connected areas) up to 13 days (in more rural locations). We outline the challenges that would likely be associated with any widespread roll-out of a smartphone-based approach such as the one described in this study, but demonstrate that in the long run the approach offers significant benefits in terms of timeliness of disease reporting, improved data integrity and greatly improved animal disease surveillance.